2016
DOI: 10.1038/tp.2015.182
|View full text |Cite
|
Sign up to set email alerts
|

Predicting early psychiatric readmission with natural language processing of narrative discharge summaries

Abstract: The ability to predict psychiatric readmission would facilitate the development of interventions to reduce this risk, a major driver of psychiatric health-care costs. The symptoms or characteristics of illness course necessary to develop reliable predictors are not available in coded billing data, but may be present in narrative electronic health record (EHR) discharge summaries. We identified a cohort of individuals admitted to a psychiatric inpatient unit between 1994 and 2012 with a principal diagnosis of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
121
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(123 citation statements)
references
References 16 publications
1
121
0
1
Order By: Relevance
“…Our NLP methods could be adapted to further explore these problems and potentially expand upon the current proposed solutions. For example, it has been shown that NLP can aid in identifying psychiatric patients at risk of early readmission from narrative discharge summaries [22]. By modifying the Sectionizer component to handle narrative discharge summaries and removing the PVS filtering in the Question-Answer-Extraction component, we could apply our methods to the task of predicting psychiatric readmission from narrative discharge summaries.…”
Section: Discussionmentioning
confidence: 99%
“…Our NLP methods could be adapted to further explore these problems and potentially expand upon the current proposed solutions. For example, it has been shown that NLP can aid in identifying psychiatric patients at risk of early readmission from narrative discharge summaries [22]. By modifying the Sectionizer component to handle narrative discharge summaries and removing the PVS filtering in the Question-Answer-Extraction component, we could apply our methods to the task of predicting psychiatric readmission from narrative discharge summaries.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [53] applied data mining techniques to build models which achieved a precision of 80% for detecting de-pression based on sentiment analysis of users on a Chinese micro-blogging platform. Rumshisky et al [42] demonstrated through a study on 4687 patients that NLP techniques such as topic modeling can be used to improve prediction of psychiatric readmission.…”
Section: Speech and Languagementioning
confidence: 99%
“…Rumshisky et al [38] predict early readmits (within 30 days) to inpatient psychiatric units through topic models built with discharge summaries. Jackson et al [17] identify over 40 key symptoms (e.g., aggression, apathy, irritability, and stupor) of severe mental illness based on discharge summaries from nearly 8000 patients visiting a UK based mental healthcare provider using SVM models.…”
Section: Related Work and Limitationsmentioning
confidence: 99%